2017
DOI: 10.2147/clep.s134603
|View full text |Cite
|
Sign up to set email alerts
|

Return to work for patients with diffuse large B-cell lymphoma and transformed indolent lymphoma undergoing autologous stem cell transplantation

Abstract: BackgroundAutologous stem cell transplantation (ASCT) is the standard treatment for patients with relapsed diffuse large B-cell lymphoma (DLBCL) or transformed indolent lymphoma (TIL). The treatment is mainly considered for younger patients still available for the work market. In this study, social outcomes after ASCT in terms of return to work (RTW) are described.Patients and methodsInformation from national administrative registers was combined with clinical information on patients, who received ASCT for rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 33 publications
0
15
1
Order By: Relevance
“…With improved remission rates, quality of life and well-being can be impacted by long-term and late effects (Leeuwen and Ng, 2017;Sarker et al, 2017). These can include persistent physical effects such as fatigue and cognition impairment (de Lima et al, 2017;Krolak et al, 2017;Leeuwen and Ng, 2017;Linendoll et al, 2016); psychosocial effects such as fear of recurrence, depression, anxiety and distress (Hall et al, 2016;van de Wal et al, 2016); along with practical concerns such as employment and finances (Arboe et al, 2017;Mojs et al, 2017). Survivors also have an increased risk of developing other diseases such as cardiovascular disease (Leeuwen and Ng, 2017) and second cancers (Leeuwen and Ng, 2017;Schaapveld et al, 2015), therefore survivors need an awareness of these potential risks to ensure timely follow-up occurs (Ng et al, 2011).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…With improved remission rates, quality of life and well-being can be impacted by long-term and late effects (Leeuwen and Ng, 2017;Sarker et al, 2017). These can include persistent physical effects such as fatigue and cognition impairment (de Lima et al, 2017;Krolak et al, 2017;Leeuwen and Ng, 2017;Linendoll et al, 2016); psychosocial effects such as fear of recurrence, depression, anxiety and distress (Hall et al, 2016;van de Wal et al, 2016); along with practical concerns such as employment and finances (Arboe et al, 2017;Mojs et al, 2017). Survivors also have an increased risk of developing other diseases such as cardiovascular disease (Leeuwen and Ng, 2017) and second cancers (Leeuwen and Ng, 2017;Schaapveld et al, 2015), therefore survivors need an awareness of these potential risks to ensure timely follow-up occurs (Ng et al, 2011).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Interestingly, relapse during the first year after allo-HSCT was not associated with full-time SL 1 year after transplantation. Previous research in autologous HSCT patients has found that relapse of the primary disease was associated with a lower likelihood of RTW in the first year after treatment [11] along with a decreased rate of RTW for patients who were on SL at the time of relapse [33]. The results suggest that those included in this study who relapsed during the first year after allo-HSCT were treated successfully, as they were able to participate in the study at the 1-year follow-up.…”
Section: Discussionmentioning
confidence: 95%
“…However, a longitudinal study found that of patients who had undergone an autologous HSCT due to relapse after treatment for lymphoma, 30% remained on SL after the first year (part-or full-time SL unknown) (n = 164) [33]. Several studies have examined RTW among HSCT patients and estimates range from 20% to approximately 45% of patients returning to full-time work 1 year after transplantation in research including both autologous and allogeneic participants [10,11,7,33]. Moreover, fewer allogeneic patients RTW within the first year after transplantation compared to autologous patients [11].…”
Section: Discussionmentioning
confidence: 99%
“…Older adults (65–85+ years) were only examined by one study 35 . Chemotherapy was the most common treatment received by participants, with two studies focusing on outcomes relating to stem cell transplantation only 36,54 …”
Section: Resultsmentioning
confidence: 99%